2013
DOI: 10.1017/s1074070800005198
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Corn Yield Response Functions to Nitrogen for Corn after Corn, Corn after Cotton, and Corn after Soybeans

Abstract: Deterministic and stochastic yield response plateau functions were estimated to determine the expected profit-maximizing nitrogen rates, yields, and net returns for corn grown after corn, cotton, and soybeans. The stochastic response functions were more appropriate than their deterministic counterparts, and the linear response stochastic plateau described the data the best. The profit-maximizing nitrogen rates were similar for corn after corn, cotton, and soybeans, but relative to corn after corn, the expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 38 publications
5
45
0
Order By: Relevance
“…Research conducted to identify the reasons for the CC yield penalty compared with CS found that corn residue accumulation in CC decreased soil N mineralization (Trinsoutrot et al, 2000), negatively affected soil temperature (Wilhelm and Wortmann, 2004), and contributed to the CC yield penalty (Gentry et al, 2013). Greater corn grain yield in CS than CC in this study is consistent with previous research (Varvel, 1994;West et al, 1996;Wilhelm and Wortmann, 2004;Wortmann et al, 2011;Boyer et al, 2013).…”
Section: Yield Traits and Harvest Indexsupporting
confidence: 88%
“…Research conducted to identify the reasons for the CC yield penalty compared with CS found that corn residue accumulation in CC decreased soil N mineralization (Trinsoutrot et al, 2000), negatively affected soil temperature (Wilhelm and Wortmann, 2004), and contributed to the CC yield penalty (Gentry et al, 2013). Greater corn grain yield in CS than CC in this study is consistent with previous research (Varvel, 1994;West et al, 1996;Wilhelm and Wortmann, 2004;Wortmann et al, 2011;Boyer et al, 2013).…”
Section: Yield Traits and Harvest Indexsupporting
confidence: 88%
“…Moreover, the economic model could be expanded by introducing stochastic weather-related variables. Agriculture is strongly influenced by seasonal, weather-related, and climate-related uncertainty [87][88][89]. Annual variation in crop yields is often explained better with annual weather-related variation in production conditions than with variation in fertilizer application rates [12,30,90].…”
Section: Discussionmentioning
confidence: 99%
“…The Tembo et al () random plateau model allows year‐to‐year variation of the yield responsiveness to nitrogen fertilizer. This model has been extensively used in the literature and some examples are Biermacher et al (), Taylor et al (), Brorsen and Richter (), Boyer et al (), Falconer et al (), and Harmon et al (). The plateau random effect allows an upward or downward shift of the average yield potential depending on the environmental condition.…”
Section: Empirical Models and Estimationmentioning
confidence: 99%